Motivational interviewing. (27th April 2010) - Rollnick, Stephen; Butler, Christopher C; Kinnersley, Paul; Gregory, John; Mash, Bob
Abstract : Motivational interviewing has been shown to promote behaviour change in a wide range of healthcare settings